Agricultural machinery workshops: design, equipment and management - Food and Agriculture Organization of the United Nations (Prepared by the Agricultural Engineering Branch. Rome, 1960)
This work deals essentially with some principles of machinery workshop location, design, management, including store-keeping and replacement parts control, and lists the essential tools and machines required to maintain in full production the field equipment used on projects
osc 29/01/2019
Loans
Keywords: Workshops; Workshops; Agricultural machinery